Triangulation scale error caused by the 1894 Shonai earthquake: a possible cause of erroneous interpretation of seismic potential along the Japan Trench - Takeshi Sagiya (Earth, Planets and Space, 2018)
Abstract Horizontal crustal strain in the Tohoku area during the twentieth century based on triangulation showed N–S extension and E–W contraction was not significant. This feature was one of the reasons why the 2011 Tohoku-oki earthquake was unexpected for many scientists. The first triangulation conducted in the late nineteenth century used a length scale defined by baseline surveys, direct measurements of short (2–10 km) baselines with steel rods. The Shionohara baseline in the Yamagata prefecture was measured in May–July 1894 and the 1894 Shonai (M7.0) earthquake occurred in its western neighbor 3 months after the measurement. The earthquake possibly elongated the baseline by as large as 5 cm or 10 ppm. However, the original length measured before the earthquake was used for the network adjustment of the entire triangulation network, causing extensive underestimation of the length scale of the network as large as 5–10 ppm in northeast Japan. The scale error effect was comparable to tectonic deformation signal over 100 years. The baseline length was re-surveyed in 2012, 1 year after the Tohoku-oki earthquake, and the result is consistent with the hypothesis of scale bias considering interseismic deformation.